GIFAP publications list - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
GIFAP (the International Group of National Associations of Manufacturers of Agrochemical Products) has issued a list of its publications. This list includes their own bimonthly bulletin, the FAO 'Code of Conduct on the distribution and use of...